Aplicación SACTEF con tecnología web para el mejoramiento del suministro de información de los contenidos temáticos de la FISI UNSM-Tarapoto - Castañeda Almeri, Santiago (2006)
SACTEF is an application with web technology to improve course content information sourcing. The Faculty of Engineering Systems and Computing (FISI) in Tarapoto’s National University (UNSM) is primarily proposing storing curriculum content to be carried out in each academic term in FISI sees great importance in being able to count on historical information and not on falsehoods, so that students can benefit. Equally, FISI proposes improving research and getting hold of curricula provided that such information sources are always appriopriate and that they integrate the usage of this aplication. In general, historical information is that which presents deficients in the aforementioned characteristics. To fulfill the proyect’s general objetive requires having a web medium which allows sourcing FISI’s curriculum information. Development of the web aplication is also needed, by periodicaly storing, each academic term, substantial up to date an organized curricula content for each subject. The course content will be provided by the respective lecturers and students (in the latter case, students’ best work and proyects). With this internet-based web technology, we want to end the traditional way of receiving course curriculum information, thereby benefiting the student in three aspects: physical, because it is a secure medium for information exchange; enthusiasm, because students receive satisfaction and want to keep up their work, and cognitive, because this information in coverted into knowledge to the advantage of the students’s academic needs. On the other hand the surveys have 100% application through a web medium which facilitates searching for and obtaining course curricula. To successfully develop the web application, that is to say its life cycle, RUP – UML is used as a model, which is specified through a sequence of diagrams: Case study diagrams, diagrams showing bussiness objetives, domain models, and collaboration diagrams, using the Rational Rose Enterprice Edition Tool. The rol of the lecturer is very important for the efficacy of the proposal because it depents of putting into practice their best proffesional intentions in developing the curriculum, requiring FISI authorit and staff cooperation. This application , which will be to the FISI’s benefit, should not be understood as a finalized creation, but rather just as a base which solves a part of the problem, to which I invite my colleagues or any others, to continue improving the application whether it be structure or presentation, with the aim of robust and efficient development and so that we can offer a good service, unfortunately until the academic term is over.